2016
DOI: 10.1371/journal.pone.0147009
|View full text |Cite
|
Sign up to set email alerts
|

The Dance of Tusks: Rediscovery of Lower Incisors in the Pan-American Proboscidean Cuvieronius hyodon Revises Incisor Evolution in Elephantimorpha

Abstract: The incisors of proboscideans (tusks and tushes) are one of the most important feature in conservation, ecology and evolutionary history of these mammals. Although the absence of upper incisors is rare in proboscideans (occurring only in deinotheres), the independent losses of lower incisors are recognized for most of its lineages (dibelodont condition). The presence of lower incisors in the Pan-American gomphothere Cuvieronius hyodon was reported a few times in literature, but it was neglected in systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…Enamel may be absent or present on the upper tusks, shaped as a single band or covering the entire tusk in juvenile and some adult individuals. The upper tusks have a circular to oval cross-section, and the lower tusks are absent (Mothé et al, 2012(Mothé et al, , 2016. In accordance with the description of the specimen from Gran Chaco province, which is slightly upcurved, not twisted, with oval cross-section outline, it is here recognized as Notiomastodon platensis, because its diagnostic features match the characteristics of the V.M.001 tusk.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Enamel may be absent or present on the upper tusks, shaped as a single band or covering the entire tusk in juvenile and some adult individuals. The upper tusks have a circular to oval cross-section, and the lower tusks are absent (Mothé et al, 2012(Mothé et al, , 2016. In accordance with the description of the specimen from Gran Chaco province, which is slightly upcurved, not twisted, with oval cross-section outline, it is here recognized as Notiomastodon platensis, because its diagnostic features match the characteristics of the V.M.001 tusk.…”
Section: Resultssupporting
confidence: 76%
“…In accordance with the description of the specimen from Gran Chaco province, which is slightly upcurved, not twisted, with oval cross-section outline, it is here recognized as Notiomastodon platensis, because its diagnostic features match the characteristics of the V.M.001 tusk. Despite the poor preservation of the tusk, we are certain that it does not represent Cuvieronius because the arrangement of the hollow dentin cones is not twisted; and they follow the configuration of the Notiomastodon platensis tusk (untwisted and even, see fig 4 of Mothé et al, 2016).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…2). Some subsequent authors agreed with the taxonomy of Osborn (Madden, 1984;Ficcarelli et al, 1995;Ferretti, 2008;Moth e et al, , 2016Lucas, 2013; Moth e and Avilla, 2015), although others did not follow the taxonomic hypothesis of Osborn (1936), accepting the presence of the genus Stegomastodon in South America (Hoffstetter, 1950(Hoffstetter, , 1952Simpson and Paula Couto, 1957;Alberdi and Prado, 1995;Shoshani and Tassy, 1996;Alberdi et al, 2002Alberdi et al, , 2004Prado et al, 2003Prado et al, , 2005Prado and Alberdi, 2008). Hoffstetter (1950) reviewed proboscideans materials from Ecuador and coined the name Haplomastodon as a subgenus of Stegomastodon.…”
Section: The Timeline Of 210 Years Of Taxonomic Issuesmentioning
confidence: 82%
“…In his review of Argentinian proboscideans, Cabrera (1929) considered Cordillerion as a junior synonym of Cuvieronius and applied this name to the Andean proboscidean, using Mastotherium hyodon as its type species, a classification followed by subsequent authors (Hoffstetter, 1950(Hoffstetter, , 1952Simpson and Paula Couto, 1957;Tobien, 1973;Shoshani and Tassy, 1996;Alberdi et al, 2002Alberdi et al, , 2004Prado et al, 2002Prado et al, , 2003Prado et al, , 2005Prado and Alberdi, 2008;Moth e et al, 2016). Lucas (2008) indicated that Cabrera (1929) probably wanted to use the oldest valid species name for what he recognized as a single South American species of Cuvieronius, even though M. humboldtii was the originally designated type species (a violation of the ICZN rules, Article 68.2 as currently articulated in ICZN, 1999).…”
Section: The Timeline Of 210 Years Of Taxonomic Issuesmentioning
confidence: 99%